Pengaruh Anonimitas dan Kecemasan Sosial terhadap Self-disclosure pada Remaja Pengguna Second account Instagram di Karawang - Najwa Saeden, Ainun; Putrie Dimala, Cempaka; Mustika, Haryanti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The use of Instagram second accounts among adolescents has increased as a means of expressing themselves more freely compared to their main accounts. This phenomenon indicates a tendency for adolescents to engage in self-disclosure on social media, which may be influenced by anonymity and social anxiety. This study aimed to analyze the influence of anonymity and social anxiety on self-disclosure among adolescent users of Instagram second accounts in Karawang Regency. The study employed a quantitative approach with a multiple linear regression design. The sample consisted of 395 adolescent Instagram second account users selected through convenience sampling. The research instruments included the Self-disclosure Scale, Perceived Anonymity Scale, and the Social Anxiety Scale for Adolescents (SAS-A). The results showed that anonymity had a significant effect on self-disclosure (p < .001), whereas social anxiety did not have a significant effect on self-disclosure (p = .255). However, anonymity and social anxiety simultaneously had a significant effect on self-disclosure (F = 19.764, p < .001). The coefficient of determination indicated that both variables contributed 9.2% to self-disclosure. These findings suggest that anonymity plays an important role in encouraging adolescents' self-disclosure on Instagram second accounts, while social anxiety does not have a significant effect.